Molecular epidemiology of hepatitis B virus infection in Switzerland: a retrospective cohort study. Issue 1 (December 2015) - Hirzel, Cédric; Wandeler, Gilles; Owczarek, Marta; Gorgievski-Hrisoho, Meri; Dufour, Jean-Francois; Semmo, Nasser; Zürcher, Samuel
Abstract Background Chronic hepatitis B virus (HBV) infection affects up to 7 % of the European population. Specific HBV genotypes are associated with rapid progression to end-stage liver disease and sub-optimal interferon treatment responses. Although the geographic distribution of HBV genotypes differs between regions, it has not been studied in Switzerland, which lies at the crossroads of Europe. Methods In a retrospective analysis of 465 HBV samples collected between 2002 and 2013, we evaluated the HBV genotype distribution and phylogenetic determinants, as well as the prevalence of serological evidence of hepatitis delta, hepatitis C and HIV infections in Switzerland. Baseline characteristics of patients were compared across their region of origin using Fisher's exact test and ANOVA, and risk factors for HBeAg positivity were assessed using logistic regression. Results The Swiss native population represented 15.7 % of HBV-infected patients living in Switzerland. In the overall population, genotype D was most prevalent (58.3 %), whereas genotype A (58.9 %) was the predominant genotype among the Swiss native population. The prevalence of patients with anti-HDV antibodies was 4.4 %. Patients of Swiss origin were most likely to be HBeAg-positive (38.1 %). HBV genotypes of patients living in Switzerland but sharing the same original region of origin were consistent with their place of birth. Conclusions The molecular epidemiology of HBV infection in Switzerland is driven by migration patterns and not by the genotype distribution of the native population. The prevalence of positive anti-HDV antibodies in our cohort was very low.